2012
DOI: 10.1161/circimaging.112.975607
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Noninvasive Characterization of Brown Adipose Tissue Blood Flow by Contrast Ultrasound in Mice

Abstract: Background Interventions to increase brown adipose tissue (BAT) volume and activation are being extensively investigated as therapies to decrease the body weight in obese subjects. Noninvasive methods to monitor these therapies in animal models and humans are rare. We investigated whether contrast ultrasound (CU) performed in mice could detect BAT and measure its activation by monitoring BAT blood flow. After validation, CU was used to study the role of uncoupling protein 1 (UCP1) and nitric oxide synthases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…The retention of 18 F-FBnTP (a mitochondria-targeting voltage sensor-radiolabeled fluorobenzyltriphenyl phosphonium) was assayed as an indicator of brown/beige fat volume and function (Madar et al 2011). A recent study describes contrast ultrasound (CU) as a novel noninvasive approach to monitor and characterize the activation of BAT in rodents based on the change of blood flow into the tissue (Baron et al 2012). It is reasonable to anticipate that other noninvasive, convenient, and sensitive measures will be developed as a better understanding of brown and beige fat biology is achieved.…”
Section: Technical Advances In Detecting Human Brown/beige Fatmentioning
confidence: 99%
“…The retention of 18 F-FBnTP (a mitochondria-targeting voltage sensor-radiolabeled fluorobenzyltriphenyl phosphonium) was assayed as an indicator of brown/beige fat volume and function (Madar et al 2011). A recent study describes contrast ultrasound (CU) as a novel noninvasive approach to monitor and characterize the activation of BAT in rodents based on the change of blood flow into the tissue (Baron et al 2012). It is reasonable to anticipate that other noninvasive, convenient, and sensitive measures will be developed as a better understanding of brown and beige fat biology is achieved.…”
Section: Technical Advances In Detecting Human Brown/beige Fatmentioning
confidence: 99%
“…Other optical approaches include imaging of BAT vasculature by using a near-infrared coupled peptide probe, which allowed visualization of both inactive and activated interscapular BAT in animal studies (99). This probe notably also labeled subcutaneous beige fat, which has proved to be that BAT activation can be monitored noninvasively by using contrast-enhanced US (93). This is supported by the observation that a norepinephrineinduced increase in BAT perfusion was blunted in mice lacking UCP1, which also fails to induce oxygen consumption and thermogenesis in response to norepinephrine (94).…”
Section: State Of the Art: Imaging Of Brown Adipose Tissuementioning
confidence: 99%
“…Although targeted tissue contrast techniques for US are still largely in the experimental stage, there is a large body of literature on the use of microbubbles for vascular contrast imaging (92). Early stage work in animals has indeed demonstrated the feasibility of microbubble contrast-enhanced US for BAT imaging (93). This approach uses brief pulses of high-energy ultrasound to locally destroy intravenously administered microbubbles, followed by dynamic imaging to monitor blood inflow (quantitated as reacquisition of microbubble-mediated contrast).…”
Section: State Of the Art: Imaging Of Brown Adipose Tissuementioning
confidence: 99%
“…AgRP, agoutirelated peptide; Cox, cyclooxygenase; GLP1, glucagon-like peptide 1; IL, interleukin; ILC2 cells, type 2 innate lymphoid cells; miRNA, micro ribonucleic acid; POMC, proopiomelanocortin; PPAR, peroxisome proliferator-activated receptors; PTEN, phosphatase and tensin homolog; TGF, transforming growth factor; TLE3, transducin-like enhancer of split 3; 5-HT1, 5-hydroxytryptamine receptor 1. (Bachman et al 2002), or by altering body temperature through the promotion of heat loss (Warner et al 2013). Moreover, at least for FGF21, it has been shown that some of the beneficial metabolic effects are in fact not dependent on UCP1 (Samms et al 2015, Veniant et al 2015.…”
Section: Ways Of Browningmentioning
confidence: 99%
“…Moreover, blood flow to BAT and WAT depots can be an important indicator of metabolic function. The use of microspheres (Foster & Frydman 1978, Rothwell & Stock 1981 and more recently microbubbles (Baron et al 2012) to measure blood flow, and therefore an approximation of oxygen consumption, can prove useful for measuring functional significance of individual tissues. Furthermore, more direct measurements of thermogenesis, for instance by recording tissue temperature (in relation to body and BAT temperature) through implantable transmitters or direct infrared thermography of fat pads, could shed light on the individual contributions to whole body thermogenesis.…”
Section: Do Beige Adipocytes Contribute To Whole Body Energy Expenditmentioning
confidence: 99%